A Brutal Unity : The Spiritual Politics of the Christian Church (Book collections on Project MUSE., 2012)
To describe the Church as "united" is a factual misnomer-even at its conception centuries ago. Ephraim Radner provides a robust rethinking of the doctrine of the church in light of Christianity's often violent and at times morally suspect history. He holds in tension the strange and transcendent oneness of God with the necessarily temporal and political function of the Church, and, in so doing, shows how the goals and failures of the liberal democratic state provide revelatory experiences that greatly enhance one's understanding of the nature of Christian unity.